38. STUDYING THE MEMORY ENHANCEMENT EFFECT OF HUP A SOFT CAPSULES USING THE SCOPOLAMINE MODEL IN MICE (Vietnam Journal of Community Medicine, 2024)
Objective: Evaluating the memory enhancing effect of Hup A soft capsules using the scopolamine model.Subject: The product used in the study is Hup A soft capsule, Enterprise standard. Methods:Mice were given Hup A at doses of 192mg and 384mg/kg/24h, then injected intraperitoneally (i.p) with 1.5 mg/kg/24h Scopolamine (Scop). Mice were tested on the Y-maze and the Morris water maze.Results: Frequency and percentage of alternation of treatment dose 2 had much higher values than Scop (p0.05). The time taken for mice to swim when finding a platform at 7th day in treatment groups 1 and 2, the Galan group, decreased differently compared to the Scop group (p
Keywords: Hup A, memory enhancement, scopolamine.